The Right to Information: Whether or not to Publish Information on Salaries of Employees Paid from Public Funds - Frumarová, Kateřina (Public Governance, Administration and Finances Law Review, 2016)
The right to information is an important instrument for a control of public authority in any democratic state. Ocasionally, however, there may be a conflict between this right and the right to privacy. In this context, the Czech Supreme Administrative Court was tasked with solving the question of whether information on the salaries of employees who are paid from public funds can be published.